FACTORS AFFECTING THE WORK STRESS OF POLICE OFFICERS: A SYSTEMATIC REVIEW - Rachma Yuniar Wijayanti; Hanandita Belva Fauzi (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2020)
Police officers are vulnerable to experience work stress, whatever the field or function they perform. The purpose of this literature study is to determine the factors that influence work stress on police officers. The journals used for review of this literature study were obtained from one portal sources, namely Google Scholar. Search journals using keywords;